THE SOCIAL FUNCTION OF TRADITIONAL POETRY OF BINI PULAU ROTE IN THE MAINTENANCE OF THE SOCIO-CULTURAL IDENTITY OF LOCAL COMMUNITIES - Yeheskial A Roen; Jeni M. Ataupah; Jacklin S. Manafe (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the social function of bini traditional poetry in the maintenance of the socio-cultural identity of local communities in Londalusi, East Rote District, Rote-Ndao Regency. The focus of the research is directed at the identification of the educational, normative, symbolic, integrative, and communicative functions of oral traditions related to the life cycle of society, including birth, marriage, and death. This study uses a qualitative approach with ethnographic-descriptive design. Data was collected through in-depth interviews and documentation of traditional narratives submitted by two key informants, namely traditional speakers (manehelo) and local traditional leaders. Data analysis was carried out thematically to map the social function of traditional narratives in the context of people's social lives. The results of the study show that traditional narratives and traditional bini poetry play an important role as a medium for inheriting traditional values, collective memory, local cosmology, and inter-generational social ethics. This oral tradition functions as a means of informal education, a regulator of social norms, a symbol of representation of the Rote people's worldview, a strengthening of social cohesion, and a cultural communication medium that maintains the continuity of the socio-cultural identity of the local community. This research confirms that the oral tradition of bini is not just an aesthetic expression, but a living and adaptive socio-cultural system. These findings contribute to strengthening the study of oral literature and cultural anthropology, especially in the context of Indonesian archipelago communities.